Trajectories of musculoskeletal shoulder pain after spinal cord injury: Identification and predictors. (May 2014) - Eriks-Hoogland, Inge E.; Hoekstra, Trynke; de Groot, Sonja; Stucki, Gerold; Post, Marcel W.; van der Woude, Lucas H.
Abstract : Objective/Background: Although shoulder pain is a problem in up to 86% of persons with a spinal cord injury (SCI), so far, no studies have empirically identified longitudinal patterns (trajectories) of musculoskeletal shoulder pain after SCI. The objective of this study was: (1) to identify distinct trajectories of musculoskeletal shoulder pain in persons with SCI, and (2) to determine possible predictors of these trajectories. Design/Methods: Multicenter, prospective cohort study in 225 newly injured persons with SCI. Outcome Measure: Shoulder pain was assessed on five occasions up to 5 years after discharge. Latent class growth mixture modeling was used to identify the distinct shoulder pain trajectories. Results: Three distinct shoulder pain trajectories were identified: (1) a "No or Low pain" trajectory (64%), (2) a "High pain" (30%) trajectory, and (3) a trajectory with a "Decrease of pain" (6%). Compared with the "No or Low pain" pain trajectory, the "High pain" trajectory consisted of more persons with tetraplegia, shoulder pain before injury, limited shoulder range of motion (ROM), lower manual muscle test scores, or more spasticity at t 1 . Multiple logistic regression analysis showed two significant predictors for the "High pain" trajectory (as compared with the "No or Low pain" trajectory): having a tetraplegia (odds ratio (OR) = 3.2; P = 0.002) and having limited shoulder ROM (OR = 2.8; P = 0.007). Conclusion: Shoulder pain in people with SCI follows distinct trajectories. At risk for belonging to the "High pain" trajectory are persons with tetraplegia and those with a limited shoulder ROM at start of active rehabilitation.